The association between food groups and childhood anemia in Zambia, based on the analysis of Zambia Demographic and Health Survey 2018 - Emi Kobayashi; Bharat Negi; Minato Nakazawa (AOSIS, 2022)
High prevalence of anemia among children has been an important public health concern globally. In Zambia, the prevalence of anemia among children aged 6-59 months was 58%. Previous studies have suggested that feeding a variety of food prevents anemia. However, it is not yet determined if out of several food groups available locally, some foods have played crucial roles in anemia among young children. The objective of this study was to find out the food groups that were associated with childhood anemia among Zambian children aged 6-59 months. We have obtained the individual-level data related to health and nutrition of the Zambia Demographic Health Survey (ZDHS) 2018 with permission. Children's feeding, demographic, and household information were analyzed using logistic regression models. Children who consumed food made from grains (AOR:1.2; 95%CI: 1.01-1.46; p=0.044) and cheese or food made from milk (AOR:2.7; 95%CI: 1.19-6.00; p=0.018) showed relatively higher prevalence of anemia than those who did not. Additionally, malnutrition, mother's anemia and education, and area of living were also significantly associated with prevalence of anemia. Most common food in Zambia is food made from grain. Grain consists of phytic acids which can prevent iron absorption. This is a potential reason for the highlevel anemia among children. Dephytinization strategies should be considered through further studies.